(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
One of the aims of the General Electrical Company of Libya (GECOL) is to supply the customers with electric energy a wording to the standard specification. Alkhoms is a Libyan city and it is one of GECOL areas. Because of the conditions increasing of the loads in Alkhoms and in all Libyan cities, the electric network should be able to feed the increasing and future loads. So it is necessary to adopt a strategic plan for future expanding of the network. The aim of this paper is to know the operating state of the electrical power system by the conditions of the power circulation, as well as developing the network until 2023 and studying the proposed solutions to solve the problems Alkhoms – Libya network. This paper has been used NEPLAN software which had estimated and solved the future expanding problems of Alkhoms networks.